Short-Time Compensation, Job Security, and Employment Contracts: Evidence from Selected OECD Countries - Van Audenrode, Marc A. (Journal of Political Economy, 1994)
In this paper, a model of optimal employment contracting describes differences across countries in firing restrictions and short-time compensation systems for workers forced to work shorter hours to avoid layoff. The model predicts that the existence of a short-time compensation (STC) system will generate major fluctuations in working hours only if the STC system is more generous than the traditional unemployment insurance system. A test performed for 10 OECD countries shows that in countries with generous STC systems, the speed of adjustment of total hours worked is higher than in the United States, despite a much slower adjustment in the number of workers employed. On the other hand, in countries with less generous STC systems, hours adjustments are far from compensating the slower employment adjustments.